Exploring the validity of a teacher language competency scale: A co-variance based approach - Mohamed Adnan, Mohamad Azrien; Mamat, Arifin; Ahmed Mohamed, Ismaiel Hassanein; Ibrahim, Mohd Burhan (Dakam, 2017)
Teacher language competency is recognized as an essential component of effective teaching. Teachers must be fluent in the four language modalities: reading, writing, listening, and speaking. In Malaysia, Arabic language has been offered to learners earlier in their schooling, prompting a demand for more Arabic language teachers who are competent in Arabic language teaching. Thus, this study aims at investigating the level of teacher language competency as well as the validity and reliability of the instrument used in assessing teacher language competency. The current study applied a stratified random sampling because of the geographical reason and involved 252 teachers out of 487 teachers from 57 National Religious Secondary Schools throughout Malaysia. The means and percentages were used to interpret the level of teacher language competency. A Structural Equation Modeling with AMOS (Analysis of Moment Structures) was employed to investigate the validity and reliability of a teacher language competency scale. The descriptive analysis showed that teachers evaluated themselves at the high level. The results of confirmatory factor analysis supported the adequacy of teacher language competency and found that the teachers’ language competency construct is a multidimensional construct with four underlying dimensions.